Prevalence of Counselling Alliance Type Preferences Across Two Samples - Bedi, Robinder P; Duff, Carlton T (Canadian Journal of Counselling and Psychotherapy, 2010)
A cross-sectional survey of two sets of counselling alliance type preferences (that were derived through past research on the client’s perspective) was conducted across two independent samples in an attempt to reliably estimate the prevalence of these client preferences and differences in their perceived importance. In particular, questionnaires were administered to determine the frequency of preferences for either a nurturant, insight-oriented, or collaborative alliance (Bachelor, 1995) and for either a personal or professional alliance (Mohr & Woodhouse, 2000; 2001). Results indicated that, depending on the sample, participants either preferred both a collaborative or insight-oriented alliance type over a nurturant one or just an insight-oriented type over a nurturant one. In addition, participants in both samples preferred a personal or professional alliance about equally. Moreover, participants believed that either Bachelor’s classification system was superior or both systems were equivalent (i.e., Mohr and Woodhouse’s system was not seen as the better system across both samples). These findings further support the existence of tangible alliance type preferences across clients. The implications of these findings for research, training and practice are discussed.